DIGITAL TRANSFORMATION IN FRANCHISE NETWORKS: LEVERAGING TECHNOLOGY TO INCREASE REVENUE AND OPERATIONAL EFFICIENCY (International Seven Journal of Multidisciplinary, 2023)
Digital transformation has reshaped organizational coordination, performance monitoring, and customer engagement across multi-unit business systems, including franchise networks. This article investigates how the adoption of enterprise resource planning systems, customer relationship management platforms, data analytics tools, automation technologies, and digital platforms contributes to operational efficiency and revenue generation in franchising. Drawing on empirical and conceptual studies in digital franchising and network governance, the paper analyzes how technological integration enhances decision-making processes, reduces coordination costs, and supports scalable growth. The findings suggest that franchise networks that successfully embed digital infrastructures into governance and operational routines demonstrate improved resource allocation, enhanced customer responsiveness, and more robust financial performance. The study contributes to the literature by examining digital transformation as a structural enabler of performance outcomes in geographically dispersed franchise systems.